PENGARUH KOMITMEN ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING (Survei Pada Karyawan Bagian Produksi PT Ventura Cahaya Mitra Sukoharjo) - Suprayitno, Desi Ratnaningrum, Alwi Suddin & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
PT Ventura Cahaya Mitra Sukoharjo as a manufacturing company in running itsoperations trying to improve employee performance. Factors affecting the performanceof employees is the organization's commitment, compensation, and organizationalcitizenship behavior. The research objective is: to analyze the significance of theinfluence of organizational commitment and compensation to organizational citizenshipbehavior. Analyze the significance of the influence of organizational commitment,compensation and organizational citizenship behavior on employee performance.Analyzing organizational citizenship behavior and organizational commitment mediatesthe effect of compensation on employee performance. This study used survey methods,the type of data used quantitative and qualitative data, the data source used primarydata and secondary data. The population in this study were all employees of theproduction of PT Ventura Cahaya Mitra Sukoharjo as many as 141 employees. Thenumber of samples in this study as many as 71 people, the sampling technique usingproportional cluster random sampling. Data collection methods are used:questionnaires and documentation. Data analysis technique used to test the validity,reliability test, classic assumption test, and path analysis. In conclusion: There was asignificant effect of organizational commitment and compensation to organizationalcitizenship behavior. There was a significant effect of organizational commitment,compensation and organizational citizenship behavior on employee performance.Organizational citizenship behavior and organizational commitment mediates the effectof compensation on employee performance.Keywords: organizational commitment, compensation, organizational citizenshipbehavior, employee performance.